Anak Usia Dini dalam Tinjauan Neuroscience dan Al-Qur’an - Sholichah, Aas Siti; Alwi, Wildan; Anshoruddin, Ahmad; Alam, Mufassirul (Prodi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas PTIQ Jakarta, 2021)
This paper aims to determine the phase of growth and development of early childhood in the study of Neuroscience and the Qur'an. The research method used is a qualitative research method with a literature study approach. In the study of Neuroscience, there is a rapid development in the 0-8 year age phase. Where the nerves of the brain function to reach 80%. The rapid development of the brain's nerves is referred to as the golden age. Where there is a golden peak of child growth and development in terms of spiritual, cognitive, language, mathematical logic, art and social emotional aspects. If parents and educators can provide stimulus and guidance properly, children will grow and develop into smart and happy children. In addition to the study of Neuroscience, this paper also explains the stages of child development in the study of the Qur'an. The term child in the Qur'an is called ash-shabi and ath-thifl, both of these terms hint at a newborn child until before puberty. The Qur'an explains that at this stage children are weak and need assistance and guidance. In addition to giving breast milk as the first and main food in the early days of birth, the guidance of Islamic law also teaches to listen to the call to prayer in the right ear, and iqamah on the left. In addition, other suggestions are aqiqah and give a good name and carry out the hitan. In addition to providing these teachings, the Qur'an gives a signal to educate children with piety and set an example of good morals.